Pemahaman Guru IPA Pra Jabatan Terhadap Mitigasi dan Isu Perubahan Iklim - Meily Putri Agustini; Meilinda Meilinda; Nyimas Aisyah; Ismet Ismet; Ida Sriyanti* (JIPI (Jurnal IPA dan Pembelajaran IPA), 2022)
Climate change is a global challenge that threatens the world today. Efforts to deal with the problem of climate change are inseparable from the extent to which individuals understand the issue of climate change. The purpose of this study was to determine the understanding of pre-service science teachers at Sriwijaya University on the issue of climate change. Data obtained through questionnaires and interviews. Data were analyzed qualitatively. The subjects of this study were 24 final semester students consisting of Physics Education, Biology Education and Chemistry Education study programs. The results showed that 1) pre-service science teachers (students) still did not explore and understand the issue of climate change where 75% of the responses of pre-service teacher students thought it was important to find solutions and understandings to overcome climate change; 2) students assume that climate change is a simple problem, this is shown from student response data, namely 59% know that increasing greenhouse gases can cause climate change. In addition, the difficulties that students experience in reducing the impact of climate change stem from behaviors that are often carried out by students in daily life such as being difficult to save electrical energy, difficult to dispose of waste according to its type. Students' understanding of climate change issues is still lacking and there needs to be awareness within each of them in order to encourage them to take climate change mitigation actions